Gender And Food: Correlation Between Women’s Participation In The Labor Force And Household Members’ Food Security - Akbarwati, Ika; Falentina, Anna T.; Yudhistira, M. Halley (Ridwan Institute, 2025)
This study examines the correlation between women’s employment and individual household members’ food security. It demonstrates that the trade-offs between women’s decision to enter the workforce and family members’ food security may depend on other factors such as household’s buying power, the existence of men’s employment within the household, and individual’s age. By utilizing the Indonesian longitudinal dataset from the Indonesia Family Life Survey (IFLS) data at the individual level and binary logistic method, this study’s results show a positive correlation between having at least one woman working in one’s household and one’s food security status. The heterogeneity analysis results clarified that employment can benefit not only the well-being of women themselves but also enhance the food security of all members of her household, without any significant difference on the income and expenditure group of the household or whether there are working men in the household.